Articulations between teaching, the anthotype and the agroecological agriculture (Revista Apotheke, 2022)
This paper seeks to think of photographic images as a field of experience and creation in education, through the historical process of photography of the nineteenth century, called anthotype, in which photographs are made with the photosensitive emulsion of vegetable pigments. Furthermore, a reflection is proposed about the artistic and educational experiences that the author has lived throughout the ongoing PHD in Media Arts research at the University of Beira Interior/UBI-Portugal, that explores the study of the anthotype and its relationship with the agroecological agriculture. Thus, is presented the reflection and the sharing of the experience around the artistic making with the anthotype process in the Photography discipline, with the students of class A of the 2nd year of the Technical Course in Audio and Video Production Integrated to High School, held in 2022/1, at Recantos da Emas Campus - Federal Institute of Education, Science and Technology of Brasilia - IFB. This classroom experience meets the concepts of expanded photography (Fernandes Junior, 2002), art as experience (Dewey, 1979) and creation processes (Salles, 2011 and 2016).
Keywords: Photography; Anthotype; Education; Experience; Creation process